Return to competitive football after major knee surgery: more questions than answers? - Bizzini, M.; Silvers, H. J. (Journal of Sports Sciences, 2014)
Despite significant advances in the diagnostics and treatment of knee injuries over the last decade, several challenges related to the subject "return to sport" remain largely unknown. For example, how should "return to sport" be defined precisely? What is the optimal timing and progression to enable a return to sport? Which criteria should be used during this process? What type of training is indicated? Which measurements can support the decision-making process? How do we optimally prepare athletes for competition without risking re-injury?